Swallow, Psyche, Persephone (On O. Mandelstam’s poem "When Psyche-life...") - HAKOBYAN, LEVON (Bulletin of Yerevan University H: Russian Philology, 2021)
In Mandelstam’s poem, "When Psyche-life..." some of the traditional mythological images undergo semantic transformations in accordance with the myth-making proclivities of early 20th century Russian literature. We examine the possible cultural and literary sources which have influenced the emergence of nontraditional interpretations of some poetic images. Specifically, we consider the mythopoetic and cultural origins of these reinterpreted images of Psyche, Persephone, the blind swallow, the green branch, and this provides an adequate interpretation of the poetic text.
Keywords: Mandelstam, Psyche, Persephone, blind swallow, green branch